Association between child's mental health and emotional maltreatment among children in out-of-home placement in Israel: importance of the child's age, poverty, domestic violence and number of maltreatment reports. Issue 4 (8th August 2022) - Ben-David, Vered
ABSTRACT: This study examines the relative importance of emotional maltreatment to predicting a child's mental health problem among 150 young children (age 0–7; M = 3.89, SD = 1.81 ) in foster care who were legally separated from their biological parents and freed for adoption by Israeli courts. 51.3% of the children were assessed with mental health problems. The study found that mental health was mostly associated with emotional maltreatment of the child. Children with a mental health diagnosis experienced more out-of-home placements, domestic violence and poverty, and had more reports of abuse and neglect compared to children without such diagnosis. The findings from a hierarchical logistic regression indicated that, after controlling for family poverty, the factors that predicted a child's mental health problems were: the number of out-of-home placements; number of maltreatment reports; domestic violence; and the child's age. Emotional maltreatment was not a significant factor. Early family intervention and less exposure to additional trauma were discussed as explanations of the findings.